Spatial distribution and antitumor activities after intratumoral injection of fragmented fibers with loaded hydroxycamptothecin. (1st September 2015) - Wei, Jiaojun; Luo, Xiaoming; Chen, Maohua; Lu, Jinfu; Li, Xiaohong
Graphical abstract: Abstract: There was only a small percentage of drug delivered to tumors after systemic administration, and solid tumors also have many barriers to prevent drug penetration within tumors. In the current study, intratumoral injection of drug-loaded fiber fragments was proposed to overcome these barriers, allowing drug accumulation at the target site to realize the therapeutic efficacy. Fragmented fibers with hydroxycamptothecin (HCPT) loaded were constructed by cryocutting of aligned electrospun fibers, and the fiber lengths of 5 (FF-5), 20 (FF-20), and 50 μm (FF-50) could be easily controlled by adjusting the slice thickness. Fragmented fibers were homogeneously dispersed into 2% sodium alginate solution, and could be smoothly injected through 26G1/2 syringe needles. FF-5, FF-20 and FF-50 fiber fragments indicated similar release profiles except a lower burst release from FF-50. In vitro viability tests showed that FF-5 and FF-20 fiber fragments caused higher cytotoxicity and apoptosis rates than FF-50. After intratumoral injection into murine H22 subcutaneous tumors, fragmented fibers with longer lengths indicated a higher accumulation into tumors and a better retention at the injection site, but showed less apparent diffusion within tumor tissues. In addition to the elimination of invasive surgery, HCPT-loaded fiber fragments showed superior in vivo antitumor activities and fewer side effects than intratumoral implantation of drug-loaded fiber mats. Compared with FF-5 and FF-50, FF-20 fiber fragments indicated optimal spatial distribution of HCPT within tumors and achieved the most significant effects on the animal survival, tumor growth inhibition and tumor cell apoptosis induction. It is suggested that the intratumoral injection of drug-loaded fiber fragments provided an efficient strategy to improve patient compliance, allow the retention of fragmented fibers and spatial distribution of drugs within tumor tissues to achieve a low systemic toxicity and an optimal therapeutic efficacy.